Navigating Job Stress: Mapping the Scientific Landscape and Charting Future Research Avenues - Josephine, Lydia; Marvianta, Y.B. Andre (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
This research aims to fill the gap in job stress studies through bibliometric analysis using metadata from Scopus and VOSviewer. The primary objective of this study is to identify key trends, significant studies, and leading authors in the job stress literature from 2014 to 2023, focusing on English-language scholarly journal publications. By employing bibliometric methods, this study will provide a comprehensive overview of the development, central themes, and theoretical dynamics in job stress research, as well as analyse citation patterns emerging in this field. Key subjects such workplace dynamics, employee well-being, stress, and psychological health, as well as workplace support and performance, are among the many methodologies and theoretical frameworks used in job stress studies that the research aims to better understand. This study will also reveal current research trends and citation patterns, providing information on the most significant studies and changes in topic focus over time. It is anticipated that the results of this study will improve knowledge of the field's general state and offer more precise guidelines for further research. In order to manage job-related stress and improve employee well-being and ultimately create healthier and more productive work environments in the future, these findings will be helpful in developing more effective ways.